2015
DOI: 10.1039/c5cp01970b
|View full text |Cite
|
Sign up to set email alerts
|

In silico phase separation in the presence of GM1 in ternary and quaternary lipid bilayers

Abstract: Cell membranes are multi-component mixtures with structural and compositional heterogeneity exhibiting a complex phase behavior. Domains formed in cell membranes often known as "Rafts" are of immense importance. Using coarse grained molecular dynamics simulations, we have studied the spontaneous phase separation of the ternary (POPC [1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine]/cholesterol/GM1) and quaternary (POPC/PSM[palmitoyl sphingomyelin]/cholesterol/GM1) lipid bilayers into liquid ordered (Lo) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…The fractional interaction matrix, also known as the preferential partitioning of membrane components represents the normalized number of contacts with a specific lipid type and has been used to study lipid phase separation into ordered and disordered domains in various bilayer systems containing peripheral and transmembrane proteins 35 , as well as phase separations 22 and lipid clustering and membrane curvature in various bilayer systems 21 . The fractional interaction matrix is calculated as pij=Cij/njΣkCik/nk …”
Section: Preferential Partitioning Of Lipids (Fractional Interaction mentioning
confidence: 99%
See 1 more Smart Citation
“…The fractional interaction matrix, also known as the preferential partitioning of membrane components represents the normalized number of contacts with a specific lipid type and has been used to study lipid phase separation into ordered and disordered domains in various bilayer systems containing peripheral and transmembrane proteins 35 , as well as phase separations 22 and lipid clustering and membrane curvature in various bilayer systems 21 . The fractional interaction matrix is calculated as pij=Cij/njΣkCik/nk …”
Section: Preferential Partitioning Of Lipids (Fractional Interaction mentioning
confidence: 99%
“…The different types of lipid clustering affect the membrane bending differently and the correlation of such lipid clustering with the membrane curvature has important biological implications 21 . For example, Ipsita et al investigated the clustering of GM1 with or without PSM using CGMD 22 . It was found that in the presence of PSM, the GM1 domains formed loosely bound clusters, whereas in the absence of PSM, they were more strongly bound in the clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Jong et al simulated sorting of proteins to liquid ordered ( L o ) domains induced by gangliosides and lipid anchors. 54 Basu et al 55 and Kociurzynski et al 56 simulated phase separation and transitions of lipid mixtures containing gangliosides.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, eight cholesterol molecules were manually docked to the acyl chains of four GM1 molecules using Hex, 42 assuming the structural influence at the interface of lipid-peptide interaction. 40,45 Additionally, seven POPG molecules were introduced to the system along with KK13, in the center of the box. 44 Herein our molecular setup also implies the equal concentration of cholesterol and GM1 on both layers.…”
Section: Computational Modelingmentioning
confidence: 99%